Clinical and morphological characteristics, management and prognosis for acute coronary syndrome in patients with type 2 diabetes mellitus - Sergey Valentinovich Kakorin; Lev Borisovich Kruglyi; Ashot Musaelovich Mkrtumyan (Сахарный диабет)
This review addresses clinical picture of acute coronary syndrome (ACS) in patients with type 2 diabetes mellitus (T2DM), the corre- sponding epidemiology data, morphological characteristics and prognosis. ACS in patients with T2DM features fulminant development, and its high lethality is due to chronic ischemic alterations in myocardium (the so-called ?metabolic ischemia?), as well as concomitant microangiopathy. It is more common for patients with T2DM to develop such complications of ACS as cardiogenic shock, acute left ventricular failure and arrhythmia that result in increased lethality during early hours of hospital admission when myocardial necrosis is yet to occur. Percutaneous translumenal intervention is by far the most effective method of ACS management in patients with T2DM. Whenever it is not available, a thrombolytic approach is indicated.